Pubertal Development Predicts Eating Behaviors in Adolescence - Baker, Jessica H. (2012)
OBJECTIVE: Early maturing girls are at increased risk for disordered eating. However, it is unclear if the association between puberty and disordered eating continues throughout pubertal development and if a similar association is exhibited in boys. METHOD: Participants included 1340 same- and 624 opposite-sex twins from the Swedish Twin Study of Child and Adolescent Development. Pubertal development was assessed at age 13–14 with the Pubertal Development Scale. General disordered eating, measured with the Eating Disorder Inventory-2 (EDI) was assessed at age 16–17, and dieting and purging behaviors were assessed at both ages 16–17 and 19–20. We applied analysis of variance and logistic regression analyses to determine whether pubertal development in early-to-mid adolescence predicted eating disorder-related behaviors in late adolescence and young adulthood RESULTS: Pubertal development in early-to-mid adolescence was significantly associated with EDI scores and dieting in late adolescence. No significant association was observed between pubertal development and dieting and purging in young adulthood. DISCUSSION: Complex combinations of cultural and biological influences likely converge during pubertal development increasing vulnerability to disordered eating. The impact of pubertal development on disordered eating appears to be limited to the adolescent period.